Peranan Teknologi Solar Cell dalam Peningkatan Daya Saing Usaha Kecil dan Menengah - Iswanto, Rif’an Tsaqif As Sadad , (Jurnal Semesta Teknika, 2011)
Rolling blackouts or blackouts caused by technical errors making people uncomfortable, one of those affected are Micro, Small and Medium Enterprises (MSMEs), due to power outages in various regions in Indonesia made a number of MSMEs to be losers. In addition to the problems faced by MSMEs is the occurrence of the peak load at night cause they can not work in the evenings (overtime). For that alternative energy is necessary for the SMEs in order to work, when electricity from PLN is susceptible to interference (fault) or in the repair process. With the considerations above, this study attempted to apply the technology Solarcell Home System (SHS) to be implemented as an energy reserve and secondary in the industrial sector, particularly in the MSMEs. The results showed that the use of technology can enhance business transformation solarcell through speed, and accuracy in producing goods. The SME entrepreneurs can increase production by using solarcell home system.